Comparison of the effect of different organic fertilizers on the availability of some nutrients and the yield of cowpeas - Alwan, Bushra M.; Al-Ogaidi, Ziyad A. Humod; Kadhim, Wejdan T.; Isa, Husian A.; Mohsen, Talib K. (International Journal of Aquatic Research and Environmental Studies, 2025)
A field experiment was conducted during the summer season of 2024 in an open farm located in Al-Tuwaitha Al-Gharbiya, near the Old Diyala Bridge in Baghdad (33°11′56″ N –44°29′30″ E), to evaluate and compare the effects of Black Soldier Fly (BSF) larvae frass with other types of organic fertilizers on the growth, yield quality, and soil nutrient availability for cowpea (Vigna unguiculata L.) grown in calcareous silty loam soil. The cowpea cultivar ‘Ramshorn’ (originating from the USA) was sown on April 2, 2024. Three types of organic fertilizers were used: BSF larvae frass, poultry manure, and cattle manure, each applied at a rate of 5 tons ha⁻¹. In addition, macronutrients (N, P, K) were applied at three levels: no addition (control), half the recommended dose, and the full recommended dose (80 kg N, 60 kg P, and 160 kg K ha⁻¹). The experiment was laid out in a factorial randomized complete block design (RCBD) with three replications. Results showed significant differences among treatments, where BSF frass—whether applied alone or combined with the full recommended NPK dose—led to superior performance in most plant and soil parameters. The highest recorded values included leaf area (120.420 cm² leaf⁻¹), shoot dry weight (79.800 g plant⁻¹), pod length (16.300 cm pod⁻¹), and cumulative yield (1.670 Mg ha⁻¹). Likewise, soil fertility indicators were enhanced, showing significant increases in available nitrogen (77.000 mg N kg⁻¹ soil), phosphorus (13.670 mg P kg⁻¹ soil), and potassium (195.730 mg K kg⁻¹ soil). The highest seed protein content (26.25%) was also recorded under the BSF frass treatment combined with the full NPK recommendation. Conclusion: BSF frass is one of the most innovative and efficient organic fertilizers derived from insect-based systems. Its rich nutrient content (N, P, K), fast decomposition due to prior digestion in the insect’s gut, and positive influence on soil health and crop productivity make it a highly sustainable alternative to conventional fertilizers. Its use contributes to enhancing soil fertility and agricultural sustainability in calcareous soils.